TM

giúp em với ạ 😭😭😭 em cảm ơn

NT
27 tháng 2 2022 lúc 15:01

\(\Leftrightarrow\left\{{}\begin{matrix}x+\dfrac{1}{3}y=\dfrac{7}{3}\\x-\dfrac{1}{2}y=-\dfrac{1}{6}\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}\dfrac{5}{6}y=\dfrac{5}{2}\\x+\dfrac{1}{3}y=\dfrac{7}{3}\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}y=3\\x=\dfrac{4}{3}\end{matrix}\right.\)

Bình luận (0)
AH
27 tháng 2 2022 lúc 15:02

Lời giải:

Lấy PT(1) trừ PT(2) theo vế:

$\frac{y}{3}+\frac{y}{2}=\frac{7}{3}+\frac{1}{6}$

$\Leftrightarrow \frac{5}{6}y=\frac{5}{2}$
$\Leftrightarrow y=3$

$x=\frac{7}{3}-\frac{y}{3}=\frac{7}{3}-1=\frac{4}{3}$

Bình luận (0)
NT
27 tháng 2 2022 lúc 15:04
Bình luận (0)

Các câu hỏi tương tự
MT
Xem chi tiết
9T
Xem chi tiết
MT
Xem chi tiết
NH
Xem chi tiết
TL
Xem chi tiết
VA
Xem chi tiết
NL
Xem chi tiết
H9
Xem chi tiết
MN
Xem chi tiết